132k views
1 vote
Simplify the expression secx/tanx

User Nicomak
by
4.8k points

2 Answers

3 votes

Answer:

csc x on edge

Step-by-step explanation:

User BoooYaKa
by
4.2k points
6 votes

sec
x
tan
x
=
csc
x

Step-by-step explanation:
Let's use the definitions of
sec
x
and
tan
x
to simplify this. We know
sec
x
=
1
cos
x
and
tan
x
=
sin
x
cos
x
. Let's plug these values into our original expression. we get
1
cos
x
sin
x
cos
x
=
1
cos
x
sin
x
cos
x

1
sin
x

csc
x

Therefore,
sec
x
tan
x
=
csc
x

Hope this helps!
User Raymel
by
4.0k points